High-risk prenatal care: Evidence for a diff erentiated approach between adult and adolescent pregnant - Reis, Diésse do Nascimento Norete; Santos, Hully Cantão dos; Traspadini, Ludmila Souza; Silva, Lauriete Carlos da; Venâncio, Fernanda Amorim; Barbosa, Míriam Carmo Rodrigues (Guará Journal, 2024)
Gestation is a natural process of the woman’s life cycle and has representations in a collective and family way. However, a number of pathological and epidemiological conditions in iso-lation or associated form confer a greater risk of negative out-comes. It was aimed to characterize the nutritional status and gestational risk factors present in adult pregnant women and adolescents assisted in a university hospital. This is a descripti-ve, quantitative cross-sectional study developed with pregnant women and adolescents attending high-risk prenatal care. The nutritional status, the socioeconomic profile characterization and the gestational risk factors were evaluated. The chi-squa-re test (X2) and Fisher’s exact test were applied. The value of p ≤ 0.05 was considered significant for all analyzes. The sample presented a statistical diff erence for: schooling, marital status and professional occupation, routing reason, pre-gravid nutri-tional status and gravid, excessive physical exertion, excessive working hours, exposure to biological, chemical and physical agents and stress. Although these are treated equally in Brazi-lian health services and protocols, adult and adolescent preg-nant women referred to high-risk care present disparities in risk manifestations.